PELAKSANAAN KEGIATAN TAHSIN AL-QUR’AN DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN BAGI ORANG DEWASA DI MASJID AL-FIRDAUS - Jahrani Jahrani; Zainap Hartati; Yuliani Khalfiah (JIP: Jurnal Ilmu Pendidikan, 2023)
This study aims to describe the background, process of implementing Qur'anic tahsin activities and improving the ability to read the Qur'an for adults through Qur'an tahsin activities at the Al-Firdaus Mosque. This research uses qualitative methods, with data collection techniques in the form of observation, interviews and documentation. The subjects of the study numbered 5 people and informants numbered 3 people. The data validation technique uses source triangulation and techniques. As well as data analysis, namely data collection, reduction, display and data conclusion drawing/verification. The results of this study show that the implementation of tahsin activities is motivated to meet learning needs and improve the reading of the Qur'an for adults, learning methods using methods; tilawati, lectures, demonstrations and questions and answers. The material using tilawati books and tajwid learning methods books as well as evaluations on volume increases in Tilawati and Qur'an tadarus books, obtained an improvement from several research subjects on the ability to read the Qur'an in aspects on makhrijul letters, Shifatul letters, Ahkamul letters and Ahkamul maddi wal qashar.